Neutrophil-to-lymphocyte ratio and its association with latent tuberculosis infection and all-cause mortality in the US adult population: a cohort study from NHANES 2011–2012 - Huang, Yingxiu; Ao, Ting; Zhen, Peng; Hu, Ming (Frontiers in Nutrition, 2024)
Background There has been little study done on the possible connection between allcause mortality and the neutrophil-to-lymphocyte ratio (NLR), particularly in individuals with latent tuberculosis infection (LTBI). The objective of this research was to examine the correlation between the NLR and LTBI, along with their effects on allcause mortality in a cohort of individuals who had either LTBI or not.Examination Survey (NHANES) 2011-2012, with a total of 4938 subjects involved. To investigate the connection between LTBI and variables, multivariable logistic regression models were used. Multivariable Cox proportional hazards models and Kaplan-Meier (KM) survival curves were employed to examine the association between NLR and all-cause death in individuals with and without LTBI.When analyzed as a continuous variable, The calculated odds ratios (ORs) for the different models-Model 1, Model 2, and Model 3 were 0.86, 0.83, and 0.84 (P<0.005). NLR was evaluated as a categorical parameter, revealing that individuals in the tertile T3 had a notably lower rate of LTBI in comparison to those in the T1 group.After adjusting for different confounders, the odds ratio for T3 varied in the various models, being 0.75 (0.60~0.95), 0.69 (0.54~0.89), and 0.71 (0.56~0.92), respectively. Additionally, higher NLR was significantly link to a greater risk of all-cause mortality in individuals with or without LTBI. Following multivariate adjustment, an 8% (Model 3, HR 1.08, 95% CI 1.05-1.12, p < 0.001) greater risk of mortality from all-cause was linked to every unit rise in NLR.3 Conclusion Results from the study revealed a negative correlation between NLR and the likelihood of LTBI as well as a higher risk of death from all causes. Therefore, NLR may be a helpful technique for risk categorization in the adult LTBI in the United States.To clarify the underlying mechanisms and any therapeutic implications of these findings, more investigation is necessary.